Analisis Linguistik Campur Kode dan Alih Kode dalam Interaksi WhatsApp Mahasiswa PBSI dan Orangtuanya - Khairunnisa Dinah; Rosmawati Harahap (Jurnal Komunitas Bahasa, 2025)
This study aims to analyze the forms and triggering factors of code-switching and code-mixing in WhatsApp communication between FKIP UMN Al-Washliyah students and their parents during the 2024–2025 academic year. Employing a descriptive qualitative approach, the data were collected from screenshots of WhatsApp conversations involving eighth-semester students of the Indonesian Language and Literature Education Study Program. Data analysis involved identifying, classifying, and describing the forms of code-switching and code-mixing, along with examining the context of their usage. The findings reveal that students, as bilingual or multilingual speakers, actively engage in code-mixing, especially by integrating regional languages into Indonesian when communicating with their parents. Code-switching was also observed, though it occurred less frequently. Additionally, mixed code-mixing and several spelling errors were found, enriching the linguistic dynamics of family communication in a digital context. These findings highlight the significant role of regional languages in maintaining identity and intimacy in students’ online interactions with family members.